Designing learning resources as classroom activities with the use of newspapers / Cheang Eng Kwong - Cheang, Eng Kwong (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
Newspapers can be a source which brings interest, excitement and relevance to our teaching. Furthermore they deal with topics which are current and of public interest. This paper highlights why the newspapers are used in the classroom and how they are properly prepared for use. It also highlights how the writer uses the newspaper articles from time to time to design versatile learning resources as teaching materials in the classroom. In addition, some suggested ways are emphasized on how the newspapers can be adopted as a learning resource. The writer hopes to convince teachers or lecturers to use newspapers to sustain students' interest in the classroom.